Relationship of School Heads’ Managerial Competencies for Promoting Positive Teacher’s Resilience in the New Normal: A Descriptive -Correlational Approach - Arlene M Aala; Lerma P Buenvinida; Consorcia S Tan; Alberto D Yazon; Karen A Manaig (International Journal of Theory and Application in Elementary and Secondary School Education, 2023)
The Philippines' current disaster mitigation and adaptation landscape this school year has brought a significant challenge to the education system as a result of the COVID-19 pandemic. Adversity and the resilience of people to hazards were experienced while combating this pandemic. Crisis and risk management systems are required to help prevent disease outbreaks and pandemics from affecting education communities. This point of view guides teachers, institutional heads, and authorities on how to deal with the crisis. The previous year saw many people face unexpected stress and adversity as a result of the worldwide outbreak of the coronavirus disease (COVID-19). As the number of challenges in providing basic education to students grows, school leaders and teachers must develop resilience in surviving and overcoming adversity. This study pursued to determine the relationship between school heads' managerial competencies to teachers' positive resilience in the new normal. A descriptive-correlational research design determined the relationship between the level of school heads' managerial competencies, and the level of teachers' positive resilience in the new normal within the four City Schools Divisions in Laguna for the school year 2021-2022. The study included 503 public school elementary teachers in the positions of teachers I-III and master teachers I-II as respondents. Using the Competency Framework for Southeast Asian School Heads (2014), and The Resilience Scale for Adults (2015), data gathering via an online platform was utilized. Frequency, percentage, mean, standard deviation, Pearson product-moment of correlation, and hierarchical linear regression were the statistical tools utilized to analyze and interpret the data gathered. Findings revealed that the school heads were practicing well in each construct of managerial competencies and each construct of positive resilience. The level of teachers' positive resilience in the new normal resulted in a very high level in terms of establishing friendly relationships easily. The researcher, therefore, concluded that when school heads demonstrated a high level of managerial competencies in terms of strategic thinking and innovation, instructional leadership, personal excellence, stakeholders' engagement, and managerial competencies, a better positive resilience may be expected to all the teachers in the new normal.